1982
DOI: 10.1152/ajpregu.1982.243.3.r347
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Osborne-Mendel and S 5B/Pl rats: effects of sucrose solutions, castration, and treatment with estradiol or insulin

Abstract: S 5B/Pl rats were tested for their susceptibility to develop obesity when 1) ovariectomized, 2) given injections of insulin, and 3) given a sucrose solution to drink instead of water. The results obtained in Osborne-Mendel rats susceptible to dietary obesity when fed a high-fat diet were compared to those obtained in the S 5B/Pl rats not susceptible to dietary obesity. When tested at the end of 10 wk, ovariectomized rats of both strains had gained 22% more weight than sham-operated controls. Replacement estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…It is, thus, possible that some of the changes in sucrose drinking observed in the present results are also due to the unconditioned regulation of food intake produced by estrogen receptor activation. Results of an earlier study showed that the unconditioned effects of estradiol on ingestion, after 5 consecutive days of estradiol injections (0.1-1 mg per rat) in OVX-female rats, were absent 3 days after cessation of treatment (Schemmel et al, 1982). This minimizes the likelihood that any unconditioned effects contributed to the observed reduction in sucrose drinking in the present study as a 5 day intertrial interval was used.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is, thus, possible that some of the changes in sucrose drinking observed in the present results are also due to the unconditioned regulation of food intake produced by estrogen receptor activation. Results of an earlier study showed that the unconditioned effects of estradiol on ingestion, after 5 consecutive days of estradiol injections (0.1-1 mg per rat) in OVX-female rats, were absent 3 days after cessation of treatment (Schemmel et al, 1982). This minimizes the likelihood that any unconditioned effects contributed to the observed reduction in sucrose drinking in the present study as a 5 day intertrial interval was used.…”
Section: Discussionmentioning
confidence: 93%
“…Conditioning Days 1-3 and the Test Day were each separated by 5 days. The results of a prior study have established that the separation period between the conditioning days and the test day in the present study is sufficient to eliminate any unconditioned effects of estradiol (Schemmel et al, 1982). Water baseline training was conducted until each animal drank a minimum of 7 ml of water in the lickometer apparatus.…”
Section: Water Deprivation and Sucrose Drinkingmentioning
confidence: 86%
“…2,3,16 There are few studies, however, that have actually compared obese to lean rats maintained on an HCD. The limited evidence indicates that hyperinsulinemia and hyperleptinemia are evident in obese animals whether on an HFD or HCD, [23][24][25] while dietary fat is a critical stimulus for producing hyperglycemia as well as hyperphagia. 26 In contrast, sucrose-or starch-rich diets reveal in obese rats increased carbohydrate metabolism in muscle, which is not evident in obese animals on an HFD.…”
Section: Introductionmentioning
confidence: 99%
“…This concern is especially valid given that intake measures were taken every 72 h and it is well known that the unconditioned effects of estradiol are observed for 24 h or more after estradiol administration and can last for days (see Geary, 2004 for review). However, it also has been reported that after 5 consecutive days of estradiol injections (0.1-1mg per rat) in OVX-female rats the unconditioned effects of estradiol on ingestion are no longer observed 3 days after the cessation of treatment (Schemmel et al, 1982). According to these results, it is highly unlikely that the present reductions in intake are solely the result of the unconditioned effects of estradiol as all experimental days were conducted 3 days apart.…”
Section: Discussionmentioning
confidence: 99%